Automatische Abstimmung der Sekundärseite eines dreiphasigen Systems zur berührungslosen induktiven Energieübertragung - Arnold, Rinaldo (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2015)
In the higher power range, three-phase inductive power transfer is an auspicious option to supply electric vehicles for local public transport. Decreases in efficiency and power transfer capability caused among others by positional misalignment and temperature cannot be completely avoided during operation. An automatic retuning of the system directly faces the remaining effects of these disturbing ascendancies and ensures continuous operation in the optimal operating point.